The Impacts of Mild Traumatic Brain Injury on Central Auditory Processing in School-Aged Children - Duquette-Laplante, Fauve (Université d'Ottawa | University of Ottawa, 2024)
The prevalence of mild traumatic brain injury (mTBI) among children has risen significantly in recent years. However, literature on hearing difficulties in children with mTBI, regardless of severity, remains scarce. Existing studies suggest that auditory processing, particularly in noisy environments like classrooms, may be impaired in these children, potentially leading to inattention behaviours post-injury. The current PhD project aimed to assess central auditory processing and listening behaviours in school-aged children with mTBI. Specifically, the project sought to (1) document functional and impaired auditory processing in this group, (2) explore children's and parents' perceptions of listening behaviours, (3) identify neurophysiological markers of auditory dysfunction post-mTBI, (4) and see if the results change over time. To answer these aims, a prospective cohort study with comparison was conducted. It was composed of two experiments: a behavioural experiment with central auditory behavioural tests, cognitive screenings, and questionnaires (self-reported and parental), and a second experiment with auditory evoked potentials in quiet and in noise with a preliminary study to establish optimal parameters for electrophysiological measurements in noise. Both experiments were carried out twice: Time 1 – shortly after mTBI diagnosis or following recruitment for controls and Time 2 – three months later to monitor symptom persistence or emergence. The findings of behavioural auditory tests revealed significant auditory impairments in temporal processing in a subset of children with a mTBI, while no neurophysiological biomarkers of mTBI could be identified in quiet or in noise. This knowledge could inform auditory evaluations following mTBI and, in turn, interventions to mitigate mTBI's impact on communication in school settings and guide post-injury rehabilitation strategies, potentially assessing recovery over time.
Keywords: Audiology; mild traumatic brain injury; mTBI; auditory processing; EEG; pediatrics